Efficacy and Safety of CAR-T Cell Products Axicabtagene Ciloleucel, Tisagenlecleucel, and Lisocabtagene Maraleucel for the Treatment of Hematologic Malignancies: A Systematic Review and Meta-Analysis - Meng, Jun; Wu, XiaoQin; Sun, Zhen; Xun, RenDe; Liu, MengSi; Hu, Rui; Huang, JianChao (Frontiers in Oncology, 2021)
Background: Currently, three chimeric antigen receptor (CAR)-T cell products axicabtagene ciloleucel, tisagenlecleucel, and lisocabtagene maraleucel have been approved by the U.S. Food and Drug Administration for the treatment of large B cell lymphoma, which provide a novel and promising choice for patients with relapsed or refractory to traditional anti-tumor treatments. Thus, it is pertinent to describe the efficacy and safety profile of the three products available by summarizing the current evidence. Methods: Two reviewers independently searched the Embase, PubMed, Web of Science, and Cochrane Library, to identify studies related to the use of the three CAR-T cell products for treating hematologic malignancies published up to October 5, 2020. We pooled the overall response rate, complete response rate, cytokine release syndrome and immune effector cell-associated neurotoxicity syndrome of three products, and then performed subgroup analysis based on the type of product and type of tumor. Results: Thirty-three studies involving 2172 patients were included in the analysis. All three products showed promising results in patients with different pathological subtypes and clinical characteristics that included those who did not meet the eligibility criteria of licensing trials, with overall response rates of nearly 70% or above and complete response rates of more than 50%. However, high rates of severe immune effector cell-associated neurotoxicity syndrome in patients undergoing axicabtagene ciloleucel treatment and life-threatening cytokine release syndrome in patients with leukemia undergoing tisagenlecleucel treatment required special attention in practice (31%; 95% CI: 0.27–0.35 and 55%; 95% CI: 0.45–0.64, respectively). Moreover, lisocabtagene maraleucel that showed a favorable efficacy and safety in the licensing trial lacked corresponding real-world data. Conclusion: Both axicabtagene ciloleucel and tisagenlecleucel showed considerable efficacy in practice, but need special attention with respect to life-threatening toxicity that can occur in certain situations. Lisocabtagene maraleucel demonstrated excellent efficacy and safety profiles in the licensing trial, but lacked corresponding real-world data. Additional data on the three products are needed in rare histological subtypes to benefit a broader patient population.